Fireclay Refractories from Ugandan Kaolinitic Minerals - Kirablra, John Baptist; Wijk, Gunnar; Jonsson, Stefan; Byaruhanga, Joseph Kadoma (steel research international, 2006)
In the present work, two deposits, one of kaolin and the other of ball clay, located in Uganda were investigated for the possibility of manufacturing fireclay refractories. Kaolin from the Mutaka deposit was used as the main source of alumina while ball clay from Mukono was the main plasticizer and binder material. The formulated green body was consolidated by wet pressing and fired at 1350°C in a tunnel kiln. Characterization of the sintered articles was done by X-ray diffraction, scanning electron microscopy, and chemical composition (ICP-AES). In addition, technological properties related to thermal conductivity, thermal shock, alkali resistance, water absorption, porosity, shrinkage, permanent linear change, linear thermal expansion, refractoriness under load, and cold crushing strength were determined. The properties of the articles manufactured from these naturally occurring raw minerals reveal that they compare favorably with those of parallel types. Thus, the raw materials can be exploited for industrial production.
Keywords: fireclay refractory, kaolin, clay.